The association between graded prognostic assessment and the prognosis of brain metastases after whole brain radiotherapy: a meta-analysis - Geng, Xiaohan; Kou, Changgui; Wang, Jianfeng (Frontiers in Oncology, 2024)
Dear Editors, Enclosed is a manuscript entitled "The association between graded prognostic assessment and the prognosis of brain metastases after whole brain radiotherapy: A meta-analysis" by Xiaohan Geng et al., which we are submitting for publication as an Original Article in Frontiers in Oncology. This study systematically evaluated and analyzed current studies to provide evidence-based medical evidence for formulating rational treatment measures and assessing patients' prognosis, the metaanalysis was used to assess the effectiveness of the graded prognostic assessment (GPA) model in reflecting the prognostic survival of patients with brain metastasis (BM) after whole brain radiotherapy (WBRT). We believe many readers will be interested in our results.